Ameliorative Effect of Fisetin on Cisplatin-Induced Nephrotoxicity in Rats via Modulation of NF-κB Activation and Antioxidant Defence - Sahu, Bidya Dhar; Kalvala, Anil Kumar; Koneru, Meghana; Mahesh Kumar, Jerald; Kuncha, Madhusudana; Rachamalla, Shyam Sunder; Sistla, Ramakrishna (PLOS ONE, 2014)
Nephrotoxicity is a dose-dependent side effect of cisplatin limiting its clinical usage in the field of cancer chemotherapy. Fisetin is a bioactive flavonoid with recognized antioxidant and anti-inflammatory properties. In the present study, we investigated the potential renoprotective effect and underlying mechanism of fisetin using rat model of cisplatin-induced nephrotoxicity. The elevation in serum biomarkers of renal damage (blood urea nitrogen and creatinine); degree of histopathological alterations and oxidative stress were significantly restored towards normal in fisetin treated, cisplatin challenged animals. Fisetin treatment also significantly attenuated the cisplatin-induced IκBα degradation and phosphorylation and blocked the NF-κB (p65) nuclear translocation, with subsequent elevation of pro-inflammatory cytokine, TNF-α, protein expression of iNOS and myeloperoxidase activities. Furthermore, fisetin markedly attenuated the translocation of cytochrome c protein from the mitochondria to the cytosol; decreased the expression of pro-apoptotic proteins including Bax, cleaved caspase-3, cleaved caspase-9 and p53; and prevented the decline of anti-apoptotic protein, Bcl-2. The cisplatin-induced mRNA expression of NOX2/gp91phox and NOX4/RENOX and the NADPH oxidase enzyme activity were also significantly lowered by fisetin treatment. Moreover, the evaluated mitochondrial respiratory enzyme activities and mitochondrial antioxidants were restored by fisetin treatment. Estimation of platinum concentration in kidney tissues revealed that fisetin treatment along with cisplatin did not alter the cisplatin uptake in kidney tissues. In conclusion, these findings suggest that fisetin may be used as a promising adjunct candidate for cisplatin use.